(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The distribution of powdery mildew on protected tomatoes was surveyed in some areas of Tartous governorate during the long season for the years 2019-2020/2020-2021. The survey showed that the protected tomatoes were infected with powdery mildew. The highest incidence of the disease was 100% over the second half of the season (Feb-June) in the Dahr Safra, Al-Anaza and Al-Souda areas. The incidence and severity of the disease was low in the first half of the season (Sept-Jan 2) during the two years of the study. The highest incidence was 12.7%, and the highest severity was 6.7% in Al-Kharab. These percentages increased in the second half of the season in all surveyed areas during the two years. The highest incidence was 85.6% in Al-Anazah area and the highest severity was 68.3 % in the Matn Al-Sahel for the year 2021. It was found by microscopic examination that the pathogens are the two species Leveillula taurica and Oidium neolycopersici. They were present in the conidial phase only, and the first one was more prevalent in different regions and throughout the season, and the second appears in three regions only, which are Al-Adamah, Al-Kharab and Matn Abu Raya, where it appeared Alone after the second cluster stage during the first half of the season, then it spread more in the second half of the season after the fourth cluster, either alone or in association with the first species in the three regions as well.